QT Interval Prolongation Associated with Intramuscular Ziprasidone in Chinese Patients: A Case Report and a Comprehensive Literature Review with Meta-Analysis - Li, Xian-Bin; Tang, Yi-Lang; Zheng, Wei; Wang, Chuan-Yue; de Leon, Jose (Case Reports in Psychiatry, 2014)
Intramuscular (IM) ziprasidone has been associated with QTc interval prolongations in patients with preexisting risk factors. A 23-year-old male Chinese schizophrenia patient experienced an increase of QTc interval of 83 milliseconds (ms) after receiving 20 mg IM ziprasidone (baseline and increased QT/QTc were, respectively, 384/418 and 450/501). This was rated as a probable adverse drug reaction (ADR) by the Liverpool ADR causality assessment tool. A systematic review including all types of trials reporting the effect of IM ziprasidone on the QTc interval prolongation identified 19 trials with a total of 1428 patients. Mean QTc change from baseline to end of each study was −3.7 to 12.8 ms after IM ziprasidone. Four randomized trials (3 of 4 published in Chinese) were used to calculate a meta-analysis of QTc interval prolongation which showed no significant differences between IM ziprasidone and IM haloperidol groups (risk ratio 0.49 to 4.31, 95% confidence interval 0.09 to 19.68, P = 0.06 to 0.41). However, our review included two cases of patients who experienced symptoms probably related to QTc prolongation after IM ziprasidone. Thus, careful screening and close monitoring, including baseline ECG, should be considered in patients receiving IM ziprasidone for the first time.